Quality of life, Risk Assessment, and Safety Research in Liver Transplantation: New Frontiers in Health Services and Outcomes Research - Butt, Zeeshan (2012)
PURPOSE OF REVIEW: In this review, we briefly summarize three fruitful, emerging areas in liver transplantation research: quality of life; risk assessment; and patient safety. Our goal is to highlight recent findings in these areas, with a call for increased integration of social scientists and transplant clinicians to address how best to shape policy and improve outcomes. RECENT FINDINGS: After liver transplantation, recipients generally experience clinically significant, sustained improvement in their physical, social and emotional well-being. However, a sizeable minority of patients do experience excess morbidity that may benefit from ongoing surveillance and/or intervention. There is growing body of research that describes risks associated with liver transplantation, which can be useful aids to better inform decision making by patients, clinicians, payers, and policy makers. In contrast, there has been a relative lack of empirical data on transplant patient safety vulnerabilities, placing the field of surgery in stark contrast to other high risk industries, where such assessments inform continuous process improvement. SUMMARY: Health services and outcomes research has grown in importance in the liver transplantation literature, but several important questions remain unanswered that merit programmatic, interdisciplinary research.